Target Identification of a 1, 3, 4‐Oxadiazin‐5(6H)‐One Anticancer Agent via Photoaffinity Labelling. Issue 9 (21st June 2019) - Lim, Bumhee; Lee, Jinah; Kim, Byungjin; Lee, Rang; Park, Jaehyun; Oh, Dong‐Chan; Gam, Jongsik; Lee, Jeeyeon
Abstract: Rational design and synthetic feasibility are critical factors for the photoaffinity labelling (PAL) approach, which can identify protein targets of bioactive small molecules under native cellular conditions. In this study, we developed photoaffinity labelling probes derived from 1, 3, 4‐oxadiazin‐5(6 H )‐ones (OPALs ) for LL‐2003, a previously reported potential anticancer agent against IGF‐1R and Src. Our photoaffinity labelling strategy enabled successful photo‐crosslinking of the probes (OPAL‐6 andOPAL‐8 ) with the target proteins in both mammalian cell lysates and live MCF7, A549, HepG2 and HeLa cells in situ . In vitro and in situ labelling demonstrated different patterns and expression levels of the proteome, and the strongest band for Src appeared in the A549 cell line. An in‐gel fluorescence scan combined with MS/MS analysis of the IGF‐1R overexpressed insect proteome labelled byOPAL‐6 andOPAL‐8 identified the binding location of the synthesized probes. Abstract : OPALs : 1, 3, 4‐Oxadiazin‐5(6 H )‐one‐based photoaffinity labelling probes (OPALs) were rationally designed and synthesized. OPALs enabled successful crosslinking with target proteins in both insect cell lysates and mammalian live cells.